An Outcome-Based Digital Learning Module for Early Childhood Teacher Education: Development and Validation Using the 4D Model - Ashari, Novita; Natsir, Tri Ayu Lestari; AT, St. Hajar Dilla; Nurzhafirah, Nurzhafirah (Al-Athfal: Jurnal Pendidikan Anak, 2025)
Purpose – This study develops and validates an Outcome-Based Education (OBE)-aligned digital learning module to enhance flexibility, interactivity, and curricular relevance in early childhood teacher education, addressing gaps in existing modules related to incomplete instructional design, weak outcome alignment, and limited responsiveness to digital learning demands.Design/methods/approach – The study employed a Research and Development (R&D) design using the 4D model: Define, Design, Develop, and Disseminate. Data were collected through expert validation sheets, questionnaires, and documentation. The module was reviewed by experts in education and educational technology and piloted with 41 students and two lecturers to assess validity, usability, and instructional feasibility. Quantitative data were analyzed using descriptive statistics and paired-sample t-tests.Findings – The findings provide context-sensitive evidence that the developed module functions as a valid, practical, and pedagogically coherent instructional resource in early childhood teacher education. Rather than suggesting that digitalization alone explains the observed gains, the results indicate that the module’s value lies in the integration of clearly specified learning outcomes, multimedia-supported delivery, and more structured student access to learning materials. The module was associated with meaningful short-term improvement in students’ cognitive performance and positive engagement during implementation, while expert review confirmed its alignment with curriculum outcomes and its suitability for the instructional context. At the same time, these findings should be interpreted with caution, as the study design does not permit strong causal claims or long-term conclusions about sustained learning impact.Research implications/limitations – This study was conducted within a single early childhood teacher education program and focused on short-term instructional outcomes; thus, findings indicate contextual promise rather than broad generalizability. Future research should examine diverse institutional and cultural settings and explore long-term impacts on pedagogical competence, learner autonomy, and teaching practice.Practical implications – The module provides a practical reference for aligning outcome-based education (OBE) with digital pedagogy in early childhood teacher education. It can support lecturers and institutions in redesigning learning materials to be more outcome-oriented, student-centered, and accessible amid curriculum reform.Originality/value – This study offers a contextually grounded framework integrating OBE, multimedia pedagogy, and student access in digital learning design. Its contribution lies in operationalizing constructive alignment in a meaningful way, providing a replicable model for reform-oriented and Global South contexts.Paper type Research paper